2018
DOI: 10.1007/s00520-018-4400-1
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of olanzapine-containing antiemetic therapy for managing highly emetogenic chemotherapy in Southeast Asia: a multinational study

Abstract: The use of olanzapine as part of standard antiemetic regimen is cost-effective for the prevention of CINV in patients receiving HEC in multiple SEA countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 23 publications
1
29
0
1
Order By: Relevance
“…Chanthawong et al reported that compared to the doublet antiemetic regimen (dexamethasone plus rstgeneration 5-HT 3 receptor antagonist), the addition of olanzapine resulted in incremental QALY of 0.0022-0.0026, with cost savings of 2.98 USD, 27.71 USD, and 52.20 USD in Thailand, Malaysia, and Indonesia, respectively [15]. At the same time, they reported that in Singapore, switching from aprepitant to olanzapine in a triplet antiemetic regimen (dexamethasone, rst-generation 5-HT 3 receptor antagonist, and aprepitant) resulted in cost savings of 60.91 USD and incremental QALYs of 0.0005 [15]. In Japan, there have been several reports examining the cost-effectiveness of aprepitant and palonosetron [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Chanthawong et al reported that compared to the doublet antiemetic regimen (dexamethasone plus rstgeneration 5-HT 3 receptor antagonist), the addition of olanzapine resulted in incremental QALY of 0.0022-0.0026, with cost savings of 2.98 USD, 27.71 USD, and 52.20 USD in Thailand, Malaysia, and Indonesia, respectively [15]. At the same time, they reported that in Singapore, switching from aprepitant to olanzapine in a triplet antiemetic regimen (dexamethasone, rst-generation 5-HT 3 receptor antagonist, and aprepitant) resulted in cost savings of 60.91 USD and incremental QALYs of 0.0005 [15]. In Japan, there have been several reports examining the cost-effectiveness of aprepitant and palonosetron [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…CR was subdivided into two mutually exclusive health outcomes: complete protection (CP), which was de ned as no emesis, rescue antiemetic therapy, and signi cant nausea, and complete response at best (CRB), which included those who achieved CR but not CP. The analysis period lasted for ve days, as in previous reports [12][13][14][15][16].…”
Section: Modelmentioning
confidence: 99%
See 3 more Smart Citations